2022
DOI: 10.1002/etc.5428
|View full text |Cite
|
Sign up to set email alerts
|

Collembola are Among the Most Pesticide‐Sensitive Soil Fauna Groups: A Meta‐Analysis

Abstract: Pesticides are a major concern because of their deleterious impacts on biodiversity and on the ecological functions provided by living organisms. Although earthworms are well studied, smaller-sized organisms, such as Collembola, also contribute to the agroecosystem functioning, and their sensitivity to pesticides makes them good bioindicators of soil quality. Using data from 21 publications, we performed a meta-analysis to compare the pesticide sensitivity of Collembola with other soil invertebrate groups and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 53 publications
(79 reference statements)
0
6
0
1
Order By: Relevance
“…No species of Collembola, Protura, or Diplura are farmed in large numbers (to our knowledge), however these groups face many of the same challenges as the wild insects. In particular, Collembola have been shown to be among the most pesticide-sensitive of all soil fauna present in high numbers in agroecosystems (Joimel et al 2022). Many pest control websites advertise the use of pesticides to control outdoor populations of Collembola in humid regions.…”
Section: Hexapodamentioning
confidence: 99%
“…No species of Collembola, Protura, or Diplura are farmed in large numbers (to our knowledge), however these groups face many of the same challenges as the wild insects. In particular, Collembola have been shown to be among the most pesticide-sensitive of all soil fauna present in high numbers in agroecosystems (Joimel et al 2022). Many pest control websites advertise the use of pesticides to control outdoor populations of Collembola in humid regions.…”
Section: Hexapodamentioning
confidence: 99%
“…Despite the use of the arti cial soil in risk assessment, even though TER-HC 5 and TER-HC 50 values were higher than the observed for the natural soil, they were still very sensitive to protect the edaphic community. Joimel et al, (2022), in a meta-analysis to compare collembola sensitivity to other soil organisms observed that collembolans are among the most sensitive organisms to pesticides and that toxicity is more pronounced in natural than in arti cial soils.…”
Section: Toxicity Exposure Ratio (Ter)mentioning
confidence: 99%
“…The diversity of mesofauna is intrinsically linked to the physical and chemical properties of the soils, making them valuable drivers of pore formation and nutrient cycling (Porre et al, 2016) but also as indicators of changes in soil properties (Pereira R de et al, 2012;Rieff et al, 2016). Their rapid response to environmental changes and sensitivity to pesticides and soil amendments make them suitable soil health indicators (Joimel et al, 2022). The Soil Biological Quality Index (BSQ) considers the presence/absence of soil mesofauna as a soil quality indicator (Parisi et al, 2005).…”
Section: Introductionmentioning
confidence: 99%